The Analysis and Improvement of User Interface Design on Climate Information Service Mobile Application Using the Lean UX Method - Muhammad Fauzi; Ni Kadek Ayu Wirdiani; Ni Kadek Dwi Rusjayanthi (Teknika, 2024)
Info BMKG is an iOS and Android app providing weather, temperature, air quality, and earthquake data across Indonesia. Issues related to the usability of the BMKG Info application were identified through observations and feedback found on the Google Play Store, which has a rating of 4.4. The responses identified included an unattractive appearance, limited features, increasing complexity, and a need for more innovation, necessitating usability evaluation and UI design improvements to enhance user experience. The analysis and redesign follow the Lean UX approach and Heuristic Evaluation method. Usability testing, specifically the Post-Study System Usability Questionnaire, is used to assess user satisfaction. The study finds that implementing Lean UX significantly improves the system's quality and user experience. UI design enhancements, based on usability testing, improve navigation, information clarity, and ease of use. Recommendations result in better outcomes, with Heuristic Evaluation yielding scores of H1 = 1 (System status visibility), H2 = 1 (Match between the system and the real world), H4 = 1 (Consistency and standards), H5 = 1 (Error prevention), H7 = 1 (Flexibility and efficiency of use), H8 = 1 (Aesthetic and minimalist design), and H9 = 1 (Help users recognize, diagnose, and recover from errors). The Post-Study System Usability Questionnaire method shows an improvement from high to a better category.